Morphological characteristics of P. xylostella granulovirus and effects on its larval host diamondback moth Plutella xylostella L. (Lepidoptera, Plutellidae) - Dezianian, Ahmed; Sajap, Ahmad Said; Lau, Wei Hong; Omar, Dzolkhifli; Abdul Kadir, Hussan; Mohamed, Rozi; Mat Yusoh, Mohamed Rani (Science Publications, 2010)
Problem Statement: Diamondback moth, Plutella xylostella L. (Lepidoptera, Plutellidae) is the most destructive insect pest of cruciferous plants throughout the world which become resistant to wide range of chemical pesticides. PxGV is known as an effective factor on diamondback moth larval mortality. Approach: Some morphological characteristics, viral DNA isolation and Restriction Endonuclease (REN) analysis of P. xylostella granulovirus and its effects of different concentrations on its larval host Diamondback Moth P. xylostella, were studied. Results: Taiwanian isolate confirmed due to restriction pattern and genome size of PxGV Taiwanian isolate which was compared with PxGV isolates reported earlier. PxGV originally isolated in Taiwan has capsules that are ovocylindrical with a mean size of 272.84Â±12 by 148.27Â±19 nm. The virions are 168.44Â±16Â±29.57Â±12 nm. Results from pathogenicity test of the granulovirus to DBM using the leaf disc method shows that first, second and third instars of P. xylostella were significantly susceptible to infection by PxGV. Older larvae were less susceptible to PxGV than younger larvae with the same virus concentration. The LC50 for second instar larvae was 1.39×106 granules mL-1. The LT50 values ranged between 3.813-6.946, 4.965-9.743 and 5145-9.407 days for first to third instars in three different concentrations, respectively. Conclusion: Its high specificity and pathogenicity to its larval host indicate that PxGV is a good candidate as an alternative biopesticide to chemical insecticides in Integrated Pest Management (IPM) of P. xylostella.